4.4.7.2 missing \(y\left ( x\right ) \) where \(x\) can also be missing or not
ode internal name "second_order_ode_missing_y"
Let \(p=y^{\prime }\) then \(y^{\prime \prime }=p^{\prime }\). Hence the ode becomes
4.4.7.2.1 Example 1
\begin{equation} y^{\prime \prime }+\left ( y^{\prime }\right ) ^{2}+y^{\prime }=0 \tag {1}\end{equation}
Let \(p=y^{\prime }\) then \(y^{\prime \prime }=p^{\prime }\). Hence the ode becomes
\begin{equation} p^{\prime }+p^{2}+p=0 \tag {2}\end{equation}
Which is now a first order separable ode. Its solution can
be easily found to be
\[ p=\frac {1}{c_{1}e^{x}-1}\]
Hence
\[ y^{\prime }\left ( x\right ) =\frac {1}{c_{1}e^{x}-1}\]
Which is now solved for \(y\left ( x\right ) \) as first order, which gives by
integration
\[ y=\ln \left ( c_{1}e^{x}-c_{2}+1\right ) -x \]
4.4.7.2.2 Example 2
\begin{align} y^{\prime \prime }+\left ( y^{\prime }\right ) ^{2} & =1\tag {1}\\ y\left ( 0\right ) & =0\nonumber \\ y^{\prime }\left ( 0\right ) & =1\nonumber \end{align}
Let \(p\left ( x\right ) =y^{\prime }\) then \(y^{\prime \prime }=p^{\prime }\) and the ode becomes
\begin{align*} p^{\prime }+p^{2} & =1\\ p^{\prime } & =1-p^{2}\\ \frac {dp}{dx} & =1-p^{2}\\ \int \frac {dp}{1-p^{2}} & =\int dx\\ \operatorname {arctanh}\left ( p\right ) & =x+c_{1}\\ p & =\tanh \left ( x+c_{1}\right ) \end{align*}
At \(x=0,p=1\) hence
\begin{equation} 1=\tanh \left ( c_{1}\right ) \nonumber \end{equation}
There is no solution. Hence no general solution exist. Now we look for singular
solution. This happens when \(1-p^{2}=0\) or \(p^{2}=1\) or \(p=\pm 1\). For \(p=1\) this means \(y^{\prime }=1\) or \(y=x+c\) which at IC gives \(c=0\). Hence singular
solution is
\[ y=x \]
This satisfies both IC’s. If we try \(p=-1\) it gives \(y=-x\) but this does not satisfy IC. So only
solution is \(y=x\).
4.4.7.2.3 Example 3A
\begin{align} y^{\prime \prime } & =\sqrt {1+\left ( y^{\prime }\right ) ^{2}}\tag {1}\\ y\left ( 0\right ) & =1\nonumber \end{align}
Notice that only one IC is given. Let \(p=y^{\prime }\) then \(y^{\prime \prime }=p^{\prime }\). Hence the ode becomes
\begin{equation} p^{\prime }=\sqrt {1+p^{2}} \tag {2}\end{equation}
We can’t use IC on
this ode, since the IC is only on \(y\) and not \(y^{\prime }\). Solving this as first order gives
\[ p\left ( x\right ) =\sinh \left ( x+c_{1}\right ) \]
But \(p=y^{\prime }\)
hence the above becomes
\[ y^{\prime }\left ( x\right ) =\sinh \left ( x+c_{1}\right ) \]
Now we solve this using the IC \(y\left ( 0\right ) =1\). Solving the above
gives
\begin{equation} y=\cosh \left ( x+c_{1}\right ) +c_{2} \tag {3}\end{equation}
Applying IC, and now we need to be careful. We need to solve for \(c_{2}\) and not
\(c_{1}\).
\begin{align*} 1 & =\cosh \left ( 0+c_{1}\right ) +c_{2}\\ c_{2} & =1-\cosh \left ( c_{1}\right ) \end{align*}
Hence (3) becomes
\[ y\left ( x\right ) =\cosh \left ( x+c_{1}\right ) +1-\cosh \left ( c_{1}\right ) \]
4.4.7.2.4 Example 3B
\begin{align} y^{\prime \prime } & =\sqrt {1+\left ( y^{\prime }\right ) ^{2}}\tag {1}\\ y\left ( 0\right ) & =1\nonumber \end{align}
This is slightly alternative way to solving the ode. Let \(p=y^{\prime }\) then \(y^{\prime \prime }=p^{\prime }\). Hence the ode becomes
\begin{equation} p^{\prime }=\sqrt {1+p^{2}} \tag {2}\end{equation}
Solving this as first order gives
\[ p\left ( x\right ) =\sinh \left ( x+c_{1}\right ) \]
But \(p=y^{\prime }\) hence the above becomes
\[ y^{\prime }\left ( x\right ) =\sinh \left ( x+c_{1}\right ) \]
Integrating gives
\begin{align} y & =\int \sinh \left ( x+c_{1}\right ) dx+c_{2}\nonumber \\ & =\cosh \left ( x+c_{1}\right ) +c_{2} \tag {3}\end{align}
Now we need to apply IC’s to find \(c_{1},c_{2}.\) We only have one IC \(y\left ( 0\right ) =1\). Applying this to the above
solution gives
\begin{align*} 1 & =\cosh \left ( c_{1}\right ) +c_{2}\\ c_{2} & =1-\cosh \left ( c_{1}\right ) \end{align*}
Hence (3) becomes
\[ y\left ( x\right ) =\cosh \left ( x+c_{1}\right ) +1-\cosh \left ( c_{1}\right ) \]
4.4.7.2.5 Example 4
\begin{align} y^{\prime \prime } & =\sqrt {1+\left ( y^{\prime }\right ) ^{2}}\tag {1}\\ y^{\prime }\left ( 0\right ) & =1\nonumber \end{align}
Notice that only one IC is given. Let \(p=y^{\prime }\) then \(y^{\prime \prime }=p^{\prime }\). Hence the ode becomes
\begin{equation} p^{\prime }=\sqrt {1+p^{2}} \tag {2}\end{equation}
Now we can use the IC
on this ode, since the IC is on \(y^{\prime }\). Solving this as first order gives
\[ p\left ( x\right ) =\sinh \left ( x+c_{1}\right ) \]
Applying IC, where \(p\left ( 0\right ) =y^{\prime }\left ( 0\right ) =1\) gives
\begin{align*} 1 & =\sinh \left ( c_{1}\right ) \\ c_{1} & =\operatorname {arcsinh}\left ( 1\right ) \end{align*}
Hence
\[ p\left ( x\right ) =\sinh \left ( x+\operatorname {arcsinh}\left ( 1\right ) \right ) \]
But \(p=y^{\prime }\) hence the above becomes
\[ y^{\prime }\left ( x\right ) =\sinh \left ( x+\operatorname {arcsinh}\left ( 1\right ) \right ) \]
Solving as first order ode gives
\[ y\left ( x\right ) =\cosh \left ( x+\ln \left ( 1+\sqrt {2}\right ) \right ) +c_{2}\]
4.4.7.2.6 Example 5
\begin{equation} y^{\prime \prime }=\left ( y^{\prime }\right ) ^{2}\cos x \tag {1}\end{equation}
Let \(p=y^{\prime }\) then \(y^{\prime \prime }=p^{\prime }\). Hence the ode becomes
\begin{align*} p^{\prime } & =p^{2}\cos x\\ \int \frac {dp}{p^{2}} & =\int \cos xdx\\ -\frac {1}{p} & =\sin x+c_{1}\end{align*}
Hence \(p=\frac {-1}{\sin x+c_{1}}\). But \(p=y^{\prime }\left ( x\right ) \). Therefore
\begin{align*} y^{\prime }\left ( x\right ) & =\frac {-1}{\sin x+c_{1}}\\ \int dy & =-\int \frac {dx}{\sin x+c_{1}}\\ y & =\frac {-\arctan \left ( \frac {2c_{1}\tan \left ( \frac {x}{2}\right ) +2}{2\sqrt {c_{1}^{2}-1}}\right ) }{\sqrt {c_{1}^{2}-1}}+c_{2}\end{align*}
4.4.7.2.7 Example 6
\begin{align} y^{\prime \prime } & =-\frac {1}{2\left ( y^{\prime }\right ) ^{2}}\tag {1}\\ y\left ( 0\right ) & =1\nonumber \\ y^{\prime }\left ( 0\right ) & =-1\nonumber \end{align}
Notice that this is also missing \(x\) type second order ode. Now let \(p\left ( x\right ) =y^{\prime }\) then \(y^{\prime \prime }=p^{\prime }\) and the ode becomes
\[ p^{\prime }=-\frac {1}{2p^{2}}\]
Which is quadrature. The solution is
\[ p^{3}+\frac {3x}{2}=c_{1}\]
At \(x=0,p\left ( 0\right ) =-1\). Hence the above gives
\[ -1=c_{1}\]
And the solution
becomes
\[ p^{3}+\frac {3x}{2}=-1 \]
But \(p=y^{\prime }\), hence the above becomes
\[ \left ( y^{\prime }\right ) ^{3}+\frac {3x}{2}=-1 \]
With IC \(y\left ( 0\right ) =1\). This is quadrature. Solving
gives
\begin{align*} y_{1} & =-\frac {1}{16}i\left ( 3x+2\right ) \left ( -i+\sqrt {3}\right ) \left ( -12x-8\right ) ^{\frac {1}{3}}+c_{1}\\ y_{2} & =\frac {1}{16}i\left ( 3x+2\right ) \left ( i+\sqrt {3}\right ) \left ( -12x-8\right ) ^{\frac {1}{3}}+c_{1}\\ y_{3} & =\frac {1}{8}\left ( 3x+2\right ) \left ( -12x-8\right ) ^{\frac {1}{3}}+c_{1}\end{align*}
Applying IC to the above shows that only second solution satisfies the original initial
conditions with \(c=\frac {3}{2}\). Hence solution is
\[ y_{2}=\frac {1}{16}\left ( 3x+2\right ) \left ( i\sqrt {3}-1\right ) \left ( -12x-8\right ) ^{\frac {1}{3}}+\frac {3}{2}\]
Another option when solving these types of odes is not
to plugin the IC until the very end. Like this. Starting with
\[ p^{3}+\frac {3x}{2}=c_{1}\]
We do not resolve
the \(c_{1}\). But keep it. Since \(p=y^{\prime }\), hence the above becomes
\[ \left ( y^{\prime }\right ) ^{3}+\frac {3x}{2}=c_{1}\]
This is quadrature. Solving
gives
\begin{align*} y_{1} & =\frac {1}{16}i\left ( 3x-2c_{1}\right ) \left ( i-\sqrt {3}\right ) \left ( 8c_{1}-12x\right ) ^{\frac {1}{3}}+c_{2}\\ y_{2} & =\frac {1}{16}i\left ( 3x-2c_{1}\right ) \left ( i+\sqrt {3}\right ) \left ( 8c_{1}-12x\right ) ^{\frac {1}{3}}+c_{2}\\ y_{3} & =\frac {1}{8}\left ( 3x-2c_{1}\right ) \left ( 8c_{1}-12x\right ) ^{\frac {1}{3}}+c_{2}\end{align*}
And only now we solve for \(c_{1},c_{2}\) from both initial conditions. Assuming we made no mistake, then
same result will come out.